From web forms to chatbots: The roles of consistency and reciprocity for user information disclosure - Adam, Martin; Benlian, Alexander (Information systems journal (Oxford, England), 2024)
Interactive decision aids (IDAs) on websites often require users to disclose relevant information (e.g., preferences, contact information) to help users in making decisions (e.g., product choice). With technological advances in IDAs, websites increasingly switch from static, non‐conversational IDAs (e.g., web forms) to conversational ones (e.g., chatbots) to boost user information disclosure that nurtures the websites' economic viability. While this novel form of IDAs is already widely employed in practice, information systems research has yet to examine the defining dialogue design features of conversational IDAs and their effects on eliciting user information. Drawing on persuasion theory and particularly on consistency and reciprocity as influence techniques, we develop a research model around two crucial dialogue design features of conversational IDAs. Specifically, we investigate the distinct and joint effects of conversational style (i.e., absence vs. presence of a conversational presentation of requests) and reciprocation triggers (i.e., absence vs. presence of reciprocity‐inducing information) on user information disclosure (i.e., email addresses). By combining the complementary properties of a randomised field experiment (N = 386) and a follow‐up online experiment (N = 182), we empirically provide evidence in support of the distinct and joint effects of conversational style and reciprocation triggers of IDAs on user information disclosure. Moreover, we demonstrate that these dialogue design features have indirect effects on information disclosure via perceptions of social presence and privacy concerns. Thus, our paper provides theoretical and practical insights into whether, how, and why critical IDA dialogue design features can better elicit user information for website services.